From Dickens to Dracula : Gothic, economics, and Victorian fiction - Houston, Gail Turley, 1950- (Cambridge studies in nineteenth-century literature and culture, 2005)
Gail Turley Houston examines how the language and imagery of economics are transformed in Gothic fiction, and traces literary and uncanny elements in economic writings of the period. This stimulating interdisciplinary book reveals that the worlds of Victorian economics and Gothic fiction, seemingly separate, actually complemented and enriched each other.